Consumer Acceptance of Green Fuel in Indian Retail Fuel Outlets : Developing a Conceptual Model Using Behavioral Reasoning Theory (BRT) - Routray, Manash; Jha, Uttam Kumar; Giri, Arunangshu (Prabandhan: Indian Journal of Management, 2025)
Purpose : Green fuel, a cleaner and environmentally friendly alternative to fossil fuels, is gaining popularity globally. Also, the increasing urgency to fight against the impact of climate change led to a growing interest in sustainable energy solutions. This research paper investigated consumers’ attitudes and adoption intentions toward green fuel in Indian retail fuel outlets using behavioral reasoning theory (BRT). It also addressed the rising demand for sustainable green fuel alternatives in India’s constantly changing automobile industry. Design/Methodology/Approach : A qualitative research design was used to develop a conceptual model in this study using BRT. Thirty-two in-depth semi-structured interviews were conducted using the convenience sampling method. This data was analyzed with the help of NVIVO 15.0 software. Findings : A conceptual model was developed to analyze the factors influencing consumer behavior towards green fuels, such as biofuels, ethanol-blended petrol, compressed natural gas (CNG), green hydrogen, and electric vehicle (EV) charging stations. The study detected prime motivators and barriers to acceptance, emphasizing the role of consumer attitude and adoption intention. This model suggested that the consumer’s motivators (“Reason For”) were environmental consciousness, health benefits, government support, and social influence, while consumer barriers (“Reason Against”) were infrastructure issues, cost concerns, and technical concerns. Implications : This study contributed to the theoretical understanding of consumers’ attitudes toward green fuel and offered actionable managerial implications for fuel retailers and policymakers to encourage sustainable energy adoption in India. Originality/Value : Unlike prior research on consumer acceptability of green fuel at retail fuel outlets, this short communication developed a conceptual model that included important drivers and constraints influencing consumer attitudes and adoption intentions for green fuel in the Indian market.